Aortic valve replacement with Dacron-supported grafts. Issue 6 (November 1968) - Watson, D. A.; Pearson, K. W.; Cawley, J. C.; Rhea, W. G.; Donnelly, R. J.; Dexter, F.
Abstract : A method is described for inserting grafts on carrier rings in the aortic area when conditions for free grafting are not applicable, namely, dilated aortic root and friable aortic wall. In addition these grafts are suitable for use in the atrio-ventricular position. The results of 11 cases are presented; one early post-operative death occurred, the follow-up period being 3 to 6 months. It is shown that this method is practicable, the incidence of post-operative aortic incompetence may be reduced, and post-operative gradients do not occur if a valve of sufficient internal diameter is used.